World-class sprinters` careers: Early success does not guarantee success at adult age - Boccia, G.; Cardinale, M.; Brustio, P. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To quantify how many of the top 50 under-18 (U18) sprinters in the world managed to become top 50 ranked as adult competitors. The authors also described the career trajectory of athletes ranked in the top 50 during either U18 or senior category. Methods: A total of 4924 male and female athletes competing in sprint races and ranked in the International Association of Athletics Federations (now World Athletics) lists in any of the seasons between the 2000 and 2018 were included in the study. The athletes ranked in the top 50 positions of all-time lists during U18, senior, or both categories were analyzed. Results: Only 17% of the male and 21% of the female top 50 ranked U18 managed to become top 50 ranked senior athletes. The top 50 ranked senior athletes consistently produced yearly larger improvements during late adolescence and early adulthood compared with those who ranked in the top 50 at U18. Furthermore, top 50 ranked senior athletes reached their peak performance later compared with the top 50 ranked only in U18. Conclusions: This study confirms that early success in track and field is not a good predictor of success at senior level in sprinting events. The yearly performance improvements and their tracking provide the most suitable approach to identify athletes more likely to succeed as elite performers in adulthood. The authors hope that the results of this study can provide useful comparative data and reference criteria for talent-identification and -development programs.